Gender-based discrimination in employment opportunities and wages distribution in Nepalese commercial bank - Yadav, Puja (Nepalese Journal of Economics, 2025)
The study examines the gender-based discrimination in employment opportunities and wages distribution in Nepalese commercial bank. Employment disparities and gender pay gap are selected as the dependent variables. The selected independent variables are educational experience, glass ceiling, work life balance, flexibility of mobility and physical and mental abilities. The primary source of data is used to assess the opinions of respondents regarding educational experience, glass ceiling, work life balance, flexibility of mobility, physical and mental abilities, employment disparities and gender pay gap. The study is based on primary data of 120 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and impacts of gender-based differences among the employees in Nepalese commercial bank. The study showed that educational experience have a positive impact on employment disparities and gender pay gap. The study also, showed that glass ceiling have positive impact on employment disparities and gender pay gap. The study also revealed that flexibility of mobility have positive impact on employment disparities and gender pay gap. Similarly, the study showed that physical and mental abilities have positive impact on employment disparities and gender pay gap. The study also showed that work life balance have positive impact on employment disparities and gender pay gap. The study also concludes that physical and mental abilities is the most influencing factor followed by educational experience and glass ceiling, that explains the effect on gender based discrimination in employment opportunities and wage distribution in Nepalese commercial bank. Similarly, the study showed that educational experience, glass ceiling, flexibility of mobility, physical and mental abilities and work life balance have a positive impact on gender pay gap.